The Level of Service Quality, Location Factor and Customer Retention in the Cinema Industry - Shaikh Talahah, Siti Nabila; Ahmad, Nurazwa; Raja Mohd Rasi, Raja Zuraidah (Research in Management of Technology and Business, 2025)
Customer retention is the long-term maintenance of commercial ties with existing customers. Customer retention is the inverse of customer turnover or defection. Low defection is equivalent to high retention. Customer retention is the maintenance of a continuous sales connection with repeat clients. The pandemic has affected the cinema business. Having been forced to temporarily close due to COVID-19 for more than a year now. Customer loyalty is a manifestation of consumer immunity. High customer retention is equivalent to immunity. This research was conducted to examine the factors that influence customer retention cinema during COVID19 pandemic which is to identify the level of the factors and customer retention. This study adopts a descriptive quantitative methods. In the meantime, the inferences used to analyze the factors that influence customer retention cinema.